Poloxamer 407 based-nanoparticles for controlled release of methotrexate - Moura, A. (2020)
Poloxamer 407 (P407)-based nanoparticles were produced by the high pressure homogenization method for the encapsulation and delivery of methotrexate (MTX), aiming intravenous therapeutic applications. The surface of these nanoparticles was functionalized by conjugation of P407 with folic acid (FA) or with MTX, which served as targeting ligand agents. MTX-P407 conjugate was also developed to increase the final drug cargo. Two hydrophobic derivatives of MTX, MTX di-ethylated ester (MTX-OEt) and the ionic complex MTX-dimethyldioctadecylammonium bromide (MTX-DODAB) were produced and entrapped onto P407-based nanoparticles. All formulations developed revealed a monodisperse character comprising small and narrow nanoparticles (<100 nm). P407 nanoparticles (functionalized with FA) and MTX-P407 nanoparticles, both loaded with MTX-OEt, demonstrated a slow drug release profile. The effect of lipase from Aspergillus oryzae on the hydrolysis of the linkage between the P407 and MTX, and consequent MTX release profile, was also evaluated. We observed a controlled and slow release of MTX (<50% of release after 11 days) in the presence of enzyme. These MTX-P407 nanoparticles loaded with MTX-OEt induced a great effect against Caco-2 cancer cells (40% of cell death after 72 h of incubation), demonstrating higher efficiency than the free MTX at the same concentration.